Efficacy of the risk score for conversion from laparoscopic to open cholecystectomy in determining the difficulty of laparoscopic cholecystectomy - Subramaniyan, Prabhakar; Iyer, Sandhya Padmanabhan; Munoli, Amar (International Surgery Journal, 2016)
Background: Laparoscopic cholecystectomy has become the treatment of choice for symptomatic cholelithiasis with ever rising numbers of surgeons receiving hands on training in its techniques and even greater numbers of patients demanding laparoscopy to avoid the discomfort and scar of open surgery. However, sometimes conversion to open cholecystectomy (OC) becomes necessary. The difficulty of LC or the risk of conversion to OC can be predicted before surgery by assessing certain preoperative variables which have been grouped together into a unified scoring system: Risk score for conversion from laparoscopic to open cholecystectomy (RSCLO). This study was undertaken to evaluate the efficacy of the RSCLO scoring system in determining the difficulty of LC and the risk of conversion to OC. Methods: This was a prospective observational study in 50 consecutive patients posted for laparoscopic cholecystectomy in a tertiary teaching hospital. All patients were evaluated using the risk score. The duration of surgery, complications and rate of conversion to open surgery was studied. Results: Male patients, patients with thickened gall bladder wall, acute cholecystitis had longer operating times and patients with high RSCLO score had a significantly longer operating time. Conclusions: The RSCLO score efficiently assesses patients posted for laparoscopic cholecystectomy with regards to difficulty and risk of conversion to open surgery.